Commercial roadmap of nanobiosensor development - Ulucan-Karnak, Fulden; Kuru, Cansu İlke; Akgöl, Sinan (Frontiers in Nanotechnology, 2024)
A nanobiosensor is a tool that converts a biological stimulus into an electrical output via nanosized transducer elements. Nanobiosensors are promising instruments, especially in biomedical applications in the literature and industry. To develop a nanobiosensor from idea to product, a life-cycle approach that comprises various processes ranging from conception through commercialization is required. Developers and potential investors should examine market requirements, design possibilities, feasibility, financial return, and risk assessments when developing a nanobiosensor development concept. It is critical to establish a well-defined regulatory pathway for bringing innovation to market at a low cost and in a short period. R&D should conduct thorough examinations of nanomaterial toxicity and health effects, involving marketing, advertising, and financial analysis. Stakeholders should discuss technology transfer office protocols for faster, healthier operations.